COMBINATION OF AHP AND MAUT METHOD TO DETERMINE SCHOLARSHIP RECIPIENTS IN HIGHER EDUCATION (CASE STUDY: UNIVERSITAS TEKNOKRAT INDONESIA) - Romdoni, Muhammad; Parjito, Parjito (Jurnal Teknik Informatika (Jutif), 2024)
Universitas Teknokrat Indonesia is an educational institution located in the city of Bandar Lampung. Every new academic year a new student admission selection is carried out. Selection is carried out with two channels, namely regular and scholarship. One of the scholarship pathways is the Indonesia Smart Lecture Card (KIP-K). The acceptance of the scholarship pathway is done conventionally. This method certainly has obstacles, namely less effective time efficiency. The solution offered is through research by applying a combination of Analytical Hierarchy Process (AHP) and Multi Attribute Utility Theory (MAUT) methods to the Decision Support System. To assist in making decisions to determine prospective students who are eligible for KIP-K Scholarships, the right criteria are needed. The criteria used include economic status, achievement, parents' income, number of dependents, housing conditions, previous scholarships, parental assistance, organizational experience, test scores, and parents' status. The purpose of this research is to apply the AHP and MAUT methods in a decision support system that can assist the campus in determining scholarship recipients quickly, precisely and efficiently. The stages of this research are data collection, application of AHP and MAUT methods, and system implementation. Based on calculations carried out using a combination of AHP and MAUT methods, the highest preference value is Destia Putri with a value of 0.7791 and the lowest preference value is Pramutya Galuh 0.0444. Judging from the ranking results, it can be concluded that the combination of AHP and MAUT methods can be used to assist in decision making to determine prospective student recipients of KIP-K scholarships at Universitas Teknokrat Indonesia.